(untitled) - Allen, Matthew (Cambridge, 1994)
This book is about the underside of Japan's economic miracle. It is an account of people who have been forgotten in Japan's push to industrialise in the post-war era: the coal-miners of Chikuho on Japan's southernmost island. The dirty and neglected character of Chikuho is in stark contrast with Japan's prevailing image as an international leader in technology and an affluent, socially cohesive country.
Keywords: Coal mines and mining